Phenols from Vaccinium dunalianum Wight: Secondary Mass Spectrometry Fragmentation and Neuroprotective Effect - ZHOU Tang, WANG Ji, QIAO Wenhao, LIN Zhiqi, ZHU Hongbo, CHANG Yue, HU Weiyan, ZHANG Rongping, CHEN Xinglong (Shipin Kexue)
In order to elucidate the health efficacy of Vaccinium dunalianum buds as a tea substitute and to reveal the material basis for its functionality, we studied the chemical constituents of V. dunalianum buds by using separation materials such as silica gel, MICHP-20p gel, Sephadex LH-20, and RP-18 combined with preparative and semi-preparative high performance liquid chromatography (HPLC), high-resolution mass spectrometry and nuclear magnetic resonance (NMR) spectroscopy. Totally 16 phenolic compounds were isolated and identified from the water extract of V. dunalianum buds, including seven arbutins, four flavonoids, two lignansand, and three other phenolic compounds, among which compounds 2–5, 7, and 11–16 were isolated from the Vaccinium genus for the first time. Secondary mass spectrometry (MS/MS) analysis revealed that the major fragmentation pathway of glycosides in the negative ion mode was the breakage of glycosidic bonds to produce fragments of aglycone or glycosyl units. Then, the aglycone or glycosyl units continued to lose neutral fragments such as H2O, CO, CHO, and CH2O to yield a series of sub-ions. Flavonoids or lignans lost their substituents such as hydroxyl, hydroxymethyl, and methoxyl groups to produce neutral fragments or additional ions. Besides, retro-Diels-Alder (RDA) fragmentation was also common in the cleavage of the flavonoid skeleton. Compounds 1–4, 6, 10 and 16 had protective effects on SH-SY5Y cells damaged by H2O2. The neuroprotective effect of compound 3 (Icariside F2) increased with increasing its concentration at 5, 10, and 20 μmol/L, and the survival rate exceeded 80% at all three concentrations. The neuroprotective effect was stronger than that of the positive drug epigallocatechin gallate. The above findings indicated that V. dunalianum buds was rich in phenolic compounds with obvious neuroprotective effects, which would expand the health functions of V. dunalianum buds as green health foods.